Convergence of media and mobile: the power of mobile marketing and the maturing mobile channel - Becker, Michael (Henry Stewart Talks, 2009)
A brand and its use of mobile, Viral web widget, Mobile has reached mass adoption, Mass media platform evolution, Introduction to the mobile channel and marketing, Mobile phone complexities, Channels, Customer lifecycle, Sources of knowledge, Guidelines, Common short code administration
Archived at 2022/04/11